Population Pharmacokinetics of Metronidazole Evaluated Using Scavenged Samples from Preterm Infants - Cohen-Wolkowiez, Michael (American Society for Microbiology, 2012)
Pharmacokinetic (PK) studies in preterm infants are rarely conducted due to the research challenges posed by this population. To overcome these challenges, minimal-risk methods such as scavenged sampling can be used to evaluate the PK of commonly used drugs in this population. We evaluated the population PK of metronidazole using targeted sparse sampling and scavenged samples from infants that were ≤32 weeks of gestational age at birth and <120 postnatal days. A 5-center study was performed. A population PK model using nonlinear mixed-effect modeling (NONMEM) was developed. Covariate effects were evaluated based on estimated precision and clinical significance. Using the individual Bayesian PK estimates from the final population PK model and the dosing regimen used for each subject, the proportion of subjects achieving the therapeutic target of trough concentrations >8 mg/liter was calculated. Monte Carlo simulations were performed to evaluate the adequacy of different dosing recommendations per gestational age group. Thirty-two preterm infants were enrolled: the median (range) gestational age at birth was 27 (22 to 32) weeks, postnatal age was 41 (0 to 97) days, postmenstrual age (PMA) was 32 (24 to 43) weeks, and weight was 1,495 (678 to 3,850) g. The final PK data set contained 116 samples; 104/116 (90%) were scavenged from discarded clinical specimens. Metronidazole population PK was best described by a 1-compartment model. The population mean clearance (CL; liter/h) was determined as 0.0397 × (weight/1.5) × (PMA/32)(2.49) using a volume of distribution (V) (liter) of 1.07 × (weight/1.5). The relative standard errors around parameter estimates ranged between 11% and 30%. On average, metronidazole concentrations in scavenged samples were 30% lower than those measured in scheduled blood draws. The majority of infants (>70%) met predefined pharmacodynamic efficacy targets. A new, simplified, postmenstrual-age-based dosing regimen is recommended for this population. Minimal-risk methods such as scavenged PK sampling provided meaningful information related to development of metronidazole PK models and dosing recommendations.